Photocatalytic Strategies for the Synthesis of Xanthates and Their Analogues - Geniller, Lilian; Taillefer, Marc; Jaroschik, Florian; Prieto, Alexis (Synthesis, 2025)
Sulfur-containing organic molecules, particularly xanthates (dithiocarbonates) and dithiocarbamates, are valuable intermediates in synthetic chemistry and the development of bioactive molecules. For instance, xanthates are potent carbon-radical precursors that can be engaged in diverse transformations, including the 1,2-difunctionalization of alkenes and other functionalizations. However, traditional synthetic methods for these compounds have been limited in efficiency and diversity. This Short Review focuses on novel photochemical procedures for generating xanthates and dithiocarbamates, discussing their advantages and disadvantages. Two main strategies emerge from the literature: (1) Three-component reactions involving the in situ formation of carbodithioate anions, and (2) two-component reactions (direct xanthylation and thiocarbamoylthiolation) using ex situ prepared xanthate and dithiocarbamate sources.1 Introduction2 Three-Component Transformations3 Two-Component Transformations4 Miscellaneous5 Conclusion
Keywords: xanthates; dithiocarbamates; thioamides; photocatalysis; radicals